Fractional-order control of a robotic bird - Couceiro, Micael S. (2009)
In this paper it is studied the relation between the angle of attack and the velocity of the bird, the tail influence over the bird trajectory, the gliding and the flapping flight in a closed loop with fractional order controllers. The results are positive for the design and construction of flying robots having similarities with flying animals. The development of computational simulation based on the dynamic of the robotic bird that should allow testing strategies and algorithms of control.